2018
DOI: 10.1016/j.ultsonch.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted synthesis of two novel [CuBr(diamine)2·H2O]Br complexes: Solvatochromism, crystal structure, physicochemical, Hirshfeld surface thermal, DNA/binding, antitumor and antibacterial activities

Abstract: Two new hydrated monocationic Cu(II) complexes with 1,3-propylenediamine and 1,2-ethylenediamine of general formula [CuBr(N-N)·HO]Br were prepared. The complexes were identified by means of several spectroscopic tools (Uv-visible, IR and MS), thermally (TG/DTA) and CHN-elemental analysis. The three dimensional structure for complex A and B was provide by X-ray diffraction studies and showed the Cu(II) ion as 4 + 1 + 1 coordinated, four nitrogen atoms of the diamine ligands, one bromide ion and one HO semi-coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…4b), which built a 3D network around the center molecule. 2,[30][31][32][33][34][35] The shortest H-bonds are identied as C]O/H-N type with 2.138 A length, followed by two -N-H/N types with 2.336 and 2.546 A which is consistent with the XRD result. No true C-H/S thiophene H-bond was detected by the Hirshfeld surface; meanwhile, XRD analysis reected such bond as H-bond with 2.993 A bond lengths.…”
Section: Crystal Interactions Hsa 2d Ngerprint (Fp) and Mep Investsupporting
confidence: 86%
See 1 more Smart Citation
“…4b), which built a 3D network around the center molecule. 2,[30][31][32][33][34][35] The shortest H-bonds are identied as C]O/H-N type with 2.138 A length, followed by two -N-H/N types with 2.336 and 2.546 A which is consistent with the XRD result. No true C-H/S thiophene H-bond was detected by the Hirshfeld surface; meanwhile, XRD analysis reected such bond as H-bond with 2.993 A bond lengths.…”
Section: Crystal Interactions Hsa 2d Ngerprint (Fp) and Mep Investsupporting
confidence: 86%
“…6d, the small bathochromic shi ($5 nm) detected between exp./DFT can be resonated to solutesolvent interactions behavior. 17,[30][31][32][33][34][35] NPA and Mulliken charges play a critical role in theoretical quantum-charge distribution; it revealed information about electrophilic and nucleophilic sited on molecule. 17,30 B3LYP/6-31G(d) Mulliken population and NPA charge analysis of the desired compound were illustrated in Fig.…”
Section: Amide Imidic Tautomerizationmentioning
confidence: 99%
“…To obtain additional information on the role played by intermolecular interactions within the crystal, a Hirshfeld surface analysis was performed [29][30][31][32]. The results are illustrated in Fig.…”
Section: Hsamentioning
confidence: 99%
“…The surface was mapped to obtain more interaction information on the molecule and its surrounding molecules in the crystal lattice that played critical roles in stabilizing the structural formula via short intermolecular forces reflected by red spot sizes on the normalized d norm [36][37][38][39][40][41]. The results illustrated in Figure 3 showed that the values of HS with three-dimensional shape and cave centers and shape ranged from 0.723 to 1.874 a.u.…”
Section: Hs and 2d-fp Investigationmentioning
confidence: 99%